Temporal muscle uptake causing an unusual focal artifact on three-dimensional stereotactic surface projections statistical maps of (18F) fluorodeoxyglucose brain positron emission tomography in a patient with Alzheimer's disease - Thientunyakit, Tanyaluck; Minoshima, Satoshi (World Journal of Nuclear Medicine, 2020)
(18F) fluorodeoxyglucose brain positron emission tomography and statistical mapping analysis, such as three-dimensional stereotactic surface projections, have been used widely for the evaluation of dementia patients. We present an unusual focal artifact on the statistical maps resulting from intense temporal muscle uptake in a patient with Alzheimer's disease. Various degrees of physiologic uptake can be seen in head and neck muscles. However, it is unusual to see a focal artifact on the statistical maps due to temporal muscle uptake. This case illustrates the importance of quality control of imaging processing when atypical findings are seen on statistical maps.
Keywords: (18F) fluorodeoxyglucose; physiologic; positron emission tomography; temporalis muscles; three-dimensional stereotactic surface projections